Karakteristik Penderita Diabetes Mellitus Dengan Komplikasi Yang Di Rawat Inap Di RSUD Deli Serdang Tahun 2012 - Fitriana Butarbutar; Hiswani .; Jemadi . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Diabetes Mellitus (DM) is a group of metabolic diseases that a problem in many countries including Indonesia. According to the American Diabetes Association (2004) the number of people with diabetes in Indonesia ranked 4th largest (8.4 million people) in the world. In North Sumatra province in 2008, prevalence of DM 1.21%. DM is known as "the great imitator" because it can affect all organs of the body and cause complications slowly. Studies using case-series design and sample size was as same as 186  equal to the number ofpopoulasi data The results showed the proportion of diabetic patients with complications of the highest in the age group 51-60 years (41.4%), female (58.6%), Malay (45.2%) Islam (75.3%), graduated primary school (40.9%), housewives work (43.5%), type 2 (96.2%), type of complications of hypertension (34.9%), chronic complications (88.2%), treatment OHO (66.1%), average length of stay (ALOS) 5.61 days (6 days), not cost alone (74.7%), outpatient home (91.4%). Statistical test results, there was no significant difference in age by sex (p = 0.720), ALOS by category of complications (p = 0.994) and there was significant difference in the ALOS based on funding source (p = 0.009). It couldn’t be performed statistical tests age bycategory of complications, categoryof complicationsby sex, category of complications based medical treatment, and category of complications based on the circumstances when home To the hospital should undergo HbA1c levels to monitor patient compliance in treatment, it is also expected pay attention to the efficiency of ALOS so that patients can be dealt with quickly and appropriately. The DM patients with complications to perform HbA1c checks, perform the recommended diet, regular exercise and taking medication on a regular basis so that blood sugar levels can be controlled to prevent more serious complications. Keywords: Characteristics, Diabetes Mellitus with Complication